Edukasi Homecare melalui Pendekatan Family Center Nursing (FCN) di Puskesmas Kabupaten Cianjur: Edukasi Homecare melalui Pendekatan Family Center Nursing (FCN) pada Perawat di Puskesmas Kabupaten Cianjur - Ummi Malikal Balqis; Ricko Dwi Hariyanto; Mona Juli Mardiansyah; Seika Linda Lestari (Ruang Ide Publisher, 2023)
Limited health services in hospitals have accelerated changes in the care environment from hospital to home, for example, home care services by nurses. Community empowerment activities through homecare education with the Family Center Nursing (FCN) approach at Cianjur District Puskesmas are an effort to accelerate family health independence in Cianjur District. This community empowerment method is an interactive lecture and discussion conducted online (zoom meeting) for nurses at the Cianjur District Puskesmas using a one group pretest-posttest design approach. Community empowerment participants were selected by purposive sampling method on nurses in Cianjur with predetermined inclusion criteria. The number of participants was 91 people. Community empowerment participants experienced an increase in knowledge about Family Center Nursing-based homecare, namely 27% of participants had good knowledge (5% previously) and 30% of participants had sufficient knowledge (26% previously). Increasing the knowledge of community empowerment participants shows that education about homecare with a family center nursing approach can be an effective choice as an effort to achieve family health independence at the Cianjur District. The results of this community empowerment are expected to be a reference for developing homecare with a family center nursing approach at puskesmas